FORMULASI HUKUM ARTIFICIAL INTELLIGENCE (AI) DALAM SISTEM KETENAGAKERJAAN INDONESIA SEBAGAI INSTRUMEN PERLINDUNGAN HAK PEKERJA - Kadek Hera Dwi Wahyuni; Anak Agung Putri Krisnadewi; I Wayan Gde Wiryawan; I Ketut Sukewati Lanang Putra Perbawa (Jurnal Yusthima, 2026)
The development of Artificial Intelligence (AI) has brought significant transformations to employment systems, ranging from recruitment processes and performance evaluation to termination of employment. On the one hand, AI offers efficiency and objectivity; on the other hand, it poses potential risks to workers’ rights, such as algorithmic discrimination, privacy violations, and job insecurity. This article aims to analyze the urgency of formulating legal regulations for the use of AI in Indonesia’s employment system as an instrument for protecting workers’ rights. The research method employed is normative legal research using statutory, conceptual, and comparative approaches. The findings indicate that Indonesia’s labor law framework has not explicitly regulated the use of AI, thereby necessitating a legal formulation grounded in the principles of the rule of law, human rights, and social justice to ensure that AI is utilized responsibly and oriented toward the protection of workers.